Implementasi Pembelajaran Berdiferensiasi Konten pada Materi Buku Fiksi dan Nonfiksi Kelas VII.8 dalam Meningkatkan Hasil belajar di SMPN 1 Masbagik - Winanda Hizby Husain; Hilmiyatun; Saufian Anhari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The implementation of differentiated instruction has become an essential strategy for accommodating students' diverse learning needs while supporting the principles of Deep Learning in the Merdeka Curriculum. This study aimed to improve the learning out-comes of seventh-grade students on fiction and non-fiction book materials through the implementation of content differentiation at SMP Negeri 1 Masbagik. The study em-ployed Classroom Action Research (CAR) consisting of two cycles, with each cycle in-cluding the stages of planning, action, observation, and reflection. The participants were 32 students of class VII.8. Data were collected through observation, learning achievement tests, and documentation, and were analyzed using descriptive quantitative and qualita-tive techniques. The findings revealed a consistent improvement in students' learning outcomes after implementing differentiated content instruction. The average learning score increased from 68 in the pre-action stage to 78 in Cycle I and further improved to 88 in Cycle II. Likewise, learning mastery increased from 59% in the pre-action stage to 78% in Cycle I and reached 91% in Cycle II. The implementation of differentiated content in-struction also enhanced students' participation, confidence, collaboration, and engage-ment during the learning process. These findings indicate that content differentiation effectively accommodates students' learning readiness and creates meaningful, active, and enjoyable learning experiences aligned with the principles of Deep Learning. There-fore, differentiated content instruction can be considered an effective learning strategy for improving students' achievement in learning fiction and non-fiction texts at the junior secondary school level.